Team Usage In Chess Instruction With Digital Technology - Bart, William (Զանգակ հրատ.)
One helpful set of resources for chess instructors is the many chess-related websites on the internet. Chess instructors may now make extensive use of this chess-related digital technology. Three case studies support the exciting phenomenon of human participants enjoying forming teams to play chess against chess bots available on chess-related websites. These teams may be viewed as cooperative groups that preferred to engage in this activity. This phenomenon occurred among school-aged children, undergraduate students, and elderly participants. One recommendation is that chess instruction involving digital technology should allow human participants to form small groups to play chess games against chess bots.
Keywords: Education